Glossário terminológico ilustrado da carpintaria naval Miriense - CORRÊA, Eledinelma Serrão (2023)
This work has as main objective the elaboration of an Illustrated Terminological Glossary of the Terminology of Naval Carpentry of Igarapé-Miri, technical vocabulary that codifies the craftsmanship of wooden vessels practiced in the Tchola Shipyard, located in the rural area of the municipality of Igarapé-Miri. This research presents a linguistic-descriptive study of the terminological variation phenomenon present in the specialized lexicon (terminology) used in the discourse of professionals (carpenter, painter and caulker) who work in the craft of naval carpentry in the aforementioned yard. The terminological work in question is organized in three conceptual fields and in a semi-systematic (alphabetical) way. The linguistic analysis of the terms was carried out based on the theoretical-methodological assumptions of socioterminology, more specifically in the studies of Enilde Faulstich (1995), Barros (2004) and Krieger and Finatto (2004). Regarding the collection of data, the following techniques were applied: interviews with informants; digital recordings; application of a semantic-lexical questionnaire (QSL); graphical transcriptions of excerpts from 07 oral narratives of the informants and capture of digital photos for illustration of the terminological glossary. The glossary has 165 entries (thermo-entry) with registry of terminological variants in its macrostructures, all taken from the oral narratives of the 07 informants listed, who present the following social stratification: a) To have more than 05 years of profession; b) Schooling: semi-literate and literate; c) To be born and raised in the researched community; with ages ranging from 18 to 40 and over 40 years. The data analysis follows the socio-terminological perspective and therefore considers the social, situational and sociolinguistic contexts in which the terms and their variants occur, with the registration of the terminological variation in the lexical, morphosyntactic, socio-professional and chronological levels, conditioned by the social factors such as schooling and function.